Analysis Of The Effect Of Green Banking On Banking Environmental And Financial Performance In Indonesia - Arif Budiarto; Ngurah Pandji Mertha Agung Durya; Alfiana; Ribka Sari Butar-Butar; Aprih Santoso (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to examine if the adoption of green banking has a sizable impact on the environmental performance of the banking industry. Organizations in Indonesia's banking industry served as the study's sample. Nonprobability sampling with purposive sampling was the strategy utilized to select the research sample. The Sustainable Finance Initiative (IKBI) program, which has 13 bank members, provided the samples for this study's banking sector companies. Quantitative research is the style used. The focus of this study's data collection strategy is on documentation and literature review. There are numerous techniques and tools for statistical testing that can be used to examine and handle research data. The Eviews application was employed as the research's analytical instrument. The implementation of green banking does not appear to have an immediate impact on banking profitability, but it is an investment that will yield significant returns in the future. The research also demonstrates that ROA does not become the only metric for evaluating the financial performance of banks that implement green banking. The effects of green banking practices by banking organizations are both immediate and long-term.